The Impact of Pro-Vulnerable Income Transfers : Leisure, Dependency and a Distribution Hypothesis - Limodio, Nicola (2012)
This paper studies a transmission mechanism through which pro-vulnerable income transfers may affect individual decision-making of non-beneficiaries in an extreme poverty context, leading to labor supply contraction and the so-called dependency syndrome. The argument is based on the distributional distortion this transfer may provoke to the relative quality of leisure, enjoyed by the population in an extreme poverty scenario. Assuming the existence of vulnerable individuals and different income groups based on certain physical, economic, or social characteristics, the author studies their decision processes and, in particular, their reactions to the aid program. The results of this theoretical research provide some insights on the conditions that an optimal pro-poor income transfer should present. A literature review is presented in support of the arguments made in the theoretical part.